The role of individual organization of circadian rhythms in the formation of carbohydrate metabolism disorders - Yu. V. Nelaeva; O. D. Rymar; I. M. Petrov; A. A. Nelaeva; A. E. Yuzhakova (Сахарный диабет)
BACKGROUND: In medical literature sources, there are data on the relationship of disorders of circadian rhythms (desynchronosis) with the development of type 2 diabetes mellitus (T2DM). Desynchronosis of circadian rhythms of glycemia can be triggered both by external factors (exposure to excessive artificial lighting in the evening, violation of the diet, «sleep-wake»), and internal — from the individual organization of circadian rhythms (chronotype). In this connection, there is an interest in the most detailed study of the influence of individual characteristics of the organization of circadian rhythms on the risk of developing T2DM. AIM: To characterize the individual organization of circadian rhythms in persons without carbohydrate metabolism disorders, with prediabetes and T2DM with obesity and BMI = 30.0–34.9 kg/m2.MATERIALS AND METHODS: Тhe Horn-Ostberg questionnaires were analyzed retrospectively in individuals with visceral obesity without carbohydrate metabolism disorders (n=40), with prediabetes (n=40) and T2DM (n=40). The results of the Horn-Ostberg test were compared with anamnestic anthropometric, laboratory parameters, nutrition diaries, daily rhythms of integral physiological indicators of carbohydrate and energy metabolism.RESULTS: All study participants (n=120) were identical age 56,7 [52,2; 58,6] years, BMI 31.3 [30.7; 33.9] kg/m2, waist circumference (OW) in women 96.54 ± 1.35 cm in men 98.75 ± 2.61 cm Sex distribution: 73% women and 27% men. Persons with morning chronotype made up 24% (29 people), intermediate 63% (75 people) and evening 13% (16 people) . In the groups, the late time for the first breakfast was noted (without carbohydrate metabolism disorders 9:45h, prediabetes 9:31 and T2DM 10:00h), and 20% of the participants missed it (p<0.05). A larger amount of daily energy value was shifted to the afternoon (p<0.05). Late bedtime was observed in all groups: without carbohydrate metabolism disorders 22.50–00.29h, with prediabetes 22.30–00.29h and T2DM 22.45–00.29h with an increase in sleep duration in the prediabetes group (08.14h, 09.00h and 08.38h, respectively). In all groups, morning and evening chronotypes had correlations with the amplitude of the daily rhythm of glycemia (r=-0.7, p=0.002 and r=-0.6, p=0.035), basal body temperature (r=0.4, p=0.046 and r=-0.5, p<0.0001) and daily energy value (r=-0.6, p= 0.041 and r=-0.6, p=0.05), differing only in the strength of the relationship.CONCLUSION: Thus, people with the morning and intermediate types of the morning chronotype, who organize a daily routine and nutrition that do not correspond to the individual characteristics of this given chronotype, can, along with people of the evening chronotype, become vulnerable in the context of the development of type 2 diabetes.